Laser-Induced Breakdown Spectroscopy (LIBS) for the Measurement of Spatial Structures and Fuel Distribution in Flames. Issue 4 (April 2016) - Kotzagianni, Maria; Kakkava, Eirini; Couris, Stelios
Laser-induced breakdown spectroscopy (LIBS) is used for the mapping of local structures (i.e., reactants and products zones) and for the determination of fuel distribution by means of the local equivalence ratio ϕ in laminar, premixed air–hydrocarbon flames. The determination of laser threshold energy to induce breakdown in the different zones of flames is employed for the identification and demarcation of the local structures of a premixed laminar flame, while complementary results about fuel concentration were obtained from measurements of the cyanogen (CN) band Β 2 Σ + –Χ 2 Σ +, (Δυ = 0) at 388.3 nm and the ratio of the atomic lines of hydrogen (Hα ) and oxygen (O(I)), Hα /O. The combination of these LIBS-based methods provides a relatively simple to use, rapid, and accurate tool for online and in situ combustion diagnostics, providing valuable information about the fuel distribution and the spatial variations of the local structures of a flame.